In Parkinson’s disease dopaminergic medication and deep brain stimulation of the subthalamic nucleus increase motor, but not reflection and cognitive impulsivity - Hendriks, Martijn; Vinke, Saman; Berlot, Rok; Benedičič, Mitja; Jahansahi, Marjan; Trošt, Maja; Georgiev, Dejan (Frontiers in Neuroscience, 2024)
Background: Parkinson's disease is associated with increased impulsivity, which can be divided into several domains: motor (consisting of proactive and reactive subdomains), reflection and cognitive impulsivity. Evidence suggests that both dopaminergic medication and subthalamic nucleus deep brain stimulation can affect impulsivity. Therefore, we set out to investigate the effect of dopaminergic medication and subthalamic nucleus deep brain stimulation on motor, reflection and cognitive impulsivity in PD patients. Methods: Twenty Parkinson's disease patients operated with subthalamic nucleus deep brain stimulation were tested ON and OFF dopaminergic medication and ON and OFF subthalamic nucleus deep brain stimulation. They performed three different impulsivity tasks: AX Continuing Performance Task to test for motor impulsivity, Beads Task for reflection impulsivity and Delay Discounting Task for cognitive impulsivity. Results: The combination of subthalamic nucleus deep brain stimulation and dopaminergic medication led to an increase in motor impulsivity (p=0.036), both proactive (p=0.045) and reactive (p=0.006). There was no effect of either dopaminergic medication or subthalamic nucleus deep brain stimulation on reflection and cognitive impulsivity. Conclusions: The combination of dopaminergic medication and subthalamic nucleus deep brain stimulation leads to increased motor, but not cognitive or reflection impulsivity in patients with Parkinson's disease. Both, proactive and reactive motor impulsivity were impaired by the combination of dopaminergic medication and subthalamic nucleus deep brain stimulation.